Prescribing Practices of Nurse Practitioners and Physician Assistants Waivered to Prescribe Buprenorphine and the Barriers They Experience Prescribing Buprenorphine. Issue 2 (25th October 2019) - Andrilla, C. Holly A.; Jones, Kendall C.; Patterson, Davis G.
Abstract: Background: In 2016, the Comprehensive Addiction Recovery Act permitted nurse practitioners (NPs) and physician assistants (PAs) to obtain a waiver to prescribe buprenorphine to treat opioid use disorder (OUD), with the goal of increasing access to this treatment. This study's purpose was to describe the buprenorphine prescribing practices of NPs and PAs and compare the barriers rural and urban providers face delivering treatment. Methods: From the October 2018 Drug Enforcement Administration list of providers with the waiver to prescribe buprenorphine, all rural NPs and PAs (1, 057) and a random sample of 500 urban NPs and PAs were surveyed. The questionnaire queried respondents about demographics, prescribing practices, practice characteristics, reimbursement policies, and barriers to prescribing buprenorphine to treat OUD. Results: Of the waivered NPs and PAs, 80.3% reported having prescribed buprenorphine and 71.1% said they were currently accepting new patients with OUD. Providers with the 30‐patient waiver were treating, on average, 13.2 patients; 37.0% were not treating any patients. The most common barrier, cited by half of providers, was concerns about diversion/medication misuse. More rural providers indicated lack of specialty backup and mental health providers as a barrier than urban providers. Never‐prescribers and former‐prescribers reported 6 barriers at significantly higher rates than did current prescribers. More rural providers accepted Medicaid and cash reimbursement than urban providers. Conclusions: NPs and PAs face many of the same barriers to providing buprenorphine as physicians have reported. Interventions to address these barriers have the potential to benefit all providers with the waiver to prescribe buprenorphine.